Producing New Spatial(Ized) (Hi)Stories on Congolese Cities: Reflections on Ten Years of Collaboration Between Ugent and Unikin - Lagae, Johan; Kivilu, Jacob Sabakinu (Afrika Focus, 2019)
This article presents the context and some of the results of ten years of collaboration in the field of African urban history between researchers from Ghent University (UGent), and mainly its Department of Architecture and Urban Planning, and scholars of the Université de Kinshasa (UNIKIN), which, in part, has benefited from the forum created by the Ghent African Platform (GAP). What ties together this collaborative work, is the conviction that ‘History matters’ when thinking not only about the past, but also about the present and the future of cities in today’s DR Congo. Moreover, we argue, it is the combination of our complementary expertise in socio-demographic history and architectural/ urban planning history that has enabled us to develop new narratives on space and society in these urban environments. These, we believe, hold a relevance for the historiography of Congo’s colonial past as well as for current discussions on colonial heritage and urban development. By demonstrating that we have gained much through stimulating a cross-disciplinary and inter-generational conversation that brings together (the expertise from) scholars working on Congo/Africa and coming from different backgrounds, academic cultures and age, we explicitly want to advocate setting up forms of relationship between the ‘North’ and ‘South’ that go beyond the common trope of ‘Capacity Building’. A number of specific pieces of work related to the cities of Kinshasa and Matadi will be discussed, illustrating how we have also deliberately sought to target different audiences by producing different kinds of output, from academic publications to exhibitions, reports for policy makers to outreach activities in the cultural arena. As such, we believe that this ten years of collaboration on African Urban History is fully in tune with GAP’s main agenda of creating a cross-disciplinary forum where scholars from North and South, and from different generations can meet and exchange ideas, and we hope to embed our future collaboration in an even broader community, both at UGent and UNIKIN. KEYWORDS: DR CONGO, URBAN HISTORY, CROSS-DISCIPLINARITY, COLLABORATIVE RESEARCH